2018
DOI: 10.1017/jfm.2018.427
|View full text |Cite
|
Sign up to set email alerts
|

Pattern formation during transition from combustion noise to thermoacoustic instability via intermittency

Abstract: Gas turbine engines are prone to the phenomenon of thermoacoustic instability, which is highly detrimental to their components. Recently, in turbulent combustors, it was observed that the transition to thermoacoustic instability occurs through an intermediate state, known as intermittency, where the system exhibits epochs of ordered behaviour, randomly appearing amidst disordered dynamics. We investigate the onset of intermittency and the ensuing self-organization in the reactive flow field, which, under certa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 78 publications
0
76
0
Order By: Relevance
“…In this figure, from the roll-up of the flame, we can discern that small-scale vortical structures exist (marked by purple circles) within the mixing layer. George et al (2018) showed that such small-scale vortical structures cause spatial and temporal incoherence in the acoustic power production.…”
Section: Multifractal Analysis Of the Flame During Combustion Noisementioning
confidence: 99%
See 1 more Smart Citation
“…In this figure, from the roll-up of the flame, we can discern that small-scale vortical structures exist (marked by purple circles) within the mixing layer. George et al (2018) showed that such small-scale vortical structures cause spatial and temporal incoherence in the acoustic power production.…”
Section: Multifractal Analysis Of the Flame During Combustion Noisementioning
confidence: 99%
“…The spatiotemporal dynamics of a turbulent combustor is largely influenced by the coupling between the various subsystems such as the hydrodynamic field, the reactive field (flame) and the acoustic field (Candel 1992). George et al (2018) showed that the emergence of order from chaos during thermoacoustic instability is the result of interactions among the patterns formed in various subsystems. The patterns formed are the standing wave pattern in the acoustic field, the large-scale coherent structures in the flow field and the coherent patterns of the flame.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the size and strength of the coherent structure are not as high as in that observed during thermoacoustic instability. George et al (2018) quantitatively measured the size of the coherent structures during the different stages of combustor operation using a vortex detection technique. Also, the strength of the coherent structure, which is reflected in the magnitude of the positive node strength, is lower than that during thermoacoustic instability.…”
Section: Spatiotemporal Evolution Of Acoustic Power Sources During Comentioning
confidence: 99%
“…The governing differential equations (16) for the sound field in a combustion chamber and 17for the tailored Green's function, have exactly the same structure, and their solutions satisfy the same boundary conditions. These features can be exploited mathematically to derive a governing integral equation for the acoustic field in terms of the tailored Green's function.…”
Section: Outline Of the Approachmentioning
confidence: 99%
“…In a further study, George et al. 16 looked in more detail into the spatio-temporal dynamics of a bluff-body stabilised turbulent combustor. They used an armoury of diagnostic equipment to measure the instantaneous local acoustic power production, p'(t)q'(x,y,t), of the flame, and applied the Mie scattering technique to reveal the interaction of vortices.…”
Section: Transition From Combustion Noise To Thermoacoustic Instabmentioning
confidence: 99%